2019
DOI: 10.5604/01.3001.0013.4463
|View full text |Cite
|
Sign up to set email alerts
|

IT Support for the Goods Reallocation Process in the Textiles-Based Fashion Retail

Abstract: The process of moving goods from locations with the weakest rotation to those with high rotation in order to speed up the process of disposing of inventory in the entire retail network can be described as an assignment of goods. This process is particularly important in the textiles- based fashion industry, where external purchases for the retail network are often made once and the goods have shallow stocks. In order to optimise the stream of materials, the use of an integrated IT system is essential. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…[5] Most of the studies previously done used synthetic dyes from petrochemical sources through hazardous chemical processes which not only became the main cause of threat to environment but also human body health is also affected. [6] The reason for increase interest to use natural dyes on account of their high compatibility with the environment as well as availability of various natural coloring resources like ,plants, minerals, fugi and animals [3]. It was earlier reported that some natural dye dyed the fabric in elegant colours but impart antibacterial and ultraviolet protection.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Most of the studies previously done used synthetic dyes from petrochemical sources through hazardous chemical processes which not only became the main cause of threat to environment but also human body health is also affected. [6] The reason for increase interest to use natural dyes on account of their high compatibility with the environment as well as availability of various natural coloring resources like ,plants, minerals, fugi and animals [3]. It was earlier reported that some natural dye dyed the fabric in elegant colours but impart antibacterial and ultraviolet protection.…”
Section: Introductionmentioning
confidence: 99%